Narkotika Menurut Pandangan Wahbah Az-Zuhaili - Mahmurudin, Mahmurudin (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2023)
Islam is a religion based on the power of reason (ratio), a person's religious values ​​are not perfect if the function of his mind is disturbed. The function of reason in Islam is very important in accepting, analyzing and believing in all the teachings received through the Qur'an, among the things that must be taken care of is that a Muslim must take care of everything that is consumed by prohibited foods such as consuming khamr/ liquor. In this research the author used quantitative methods. The results of this research are that khamr has the same legal status as narcotics.